Cientometria aplicada a materiais para armazenamento de hidrogênio - Chanchetti, Lucas Faccioni (2014)
Fossil Fuels have been used for more than a century as energy sources and vectors. Albeit their high energy densities and easy transport and containment, their availability is limited and they are notorious local pollution and global warming drivers, delivering no sustainability. Hydrogen Fuel Cells are a promising alternative for its substitution. However, more technological development is necessary for the production, conversion and especially for the storage of Hydrogen. Several materials absorb hydrogen, storing it through physical or chemical bonds. Innumerous research efforts have been conducted for the discovery of new such materials and for the enhancement of their hydrogen storage properties. The present work attempted to quantify these efforts through Scientometrics, revealing their time evolution, main material classes and work strategies of countries and institutions. Scientific Publications in the field were collected and processed by Text Mining associated with Bibliometrics. Technological Indicators were elaborated and analyzed with Technological Forecasting and Competitive Intelligence tools. We mapped the time evolution of the publications in the field, in the Materials Classes and in the main countries, the concentration of efforts per Country, and the main Institutions per Materials Class. From 2010 we observed a reduction in the number of Publications, related to the frustration of the exaggerated expectancies generated in the previous decade s Hydrogen Hype, associated with the transfer of efforts to Battery based Electrical and Hybrid Vehicles. Among the Materials classes, Metal Organic Frameworks stood out for their highest number of publications and growth, although its research only recently gained momentum. The main Countries were split into those that showed a recent growth in the number of publications and those that stagnated after 2010. From the general analysis of the field and the strategies of the main countries and research institutions, we expect to support decision making in the field, concerning amongst others: the allocation of human and monetary resources, effort directing, partnership formation and benchmarking.